Peningkatan Karakter Kejujuran dan Bekerjasama Anak melalui Permainan Tradisional Cublak-Cublak Suweng di TK Rejosari - Lestari, Lestari; Hanif, Muhammad; Sudarmiani, Sudarmiani (YASIN, 2025)
The low levels of cooperation and honesty among Group B children at TK Rejosari, where 80% of students achieved only the One-Star level in developmental outcomes. The lack of group learning activities that incorporate local wisdom values further exacerbates this condition. This study aims to enhance children’s character traits of honesty and cooperation through the implementation of the traditional game Cublak-Cublak Suweng. The research employed Classroom Action Research (CAR), conducted over two cycles involving 20 Group B students. Data were collected through observation and documentation and analyzed descriptively. The results show a significant improvement in cooperative behavior, increasing from 7.5% in the initial condition to 35% in Cycle I, and reaching 80% in Cycle II. Honesty also improved, rising from 13.75% to 36.25% in Cycle I, and reaching 86.25% in Cycle II. The study concludes that the traditional game Cublak-Cublak Suweng is effective in fostering honesty and cooperation among early childhood learners. It recommends the integration of traditional games as a character education medium in early childhood education (ECE) settings.